Novel treatment options for juvenile idiopathic arthritis. Issue 5 (September 2015) - Steigerwald, Katherine A; Ilowite, Norman T
<x xml:space="preserve">Abstract</x> The purpose of this review is to summarize the newer and possible future treatments for the arthritis and systemic features in children with juvenile idiopathic arthritis (JIA), including evidence supporting their efficacy and safety.